La presse hellénique d’expression française à Paris et la promotion de la Grèce moderne (fin xixe-début xxe siècle) - Despina Provata (Cahiers Balkaniques)
In the second part of the nineteenth century, the Greek press published in Paris, which until then had been written in Greek, gradually adopts French. This choice can be attributed to the fact that the French media landscape after 1881 was favourable to the publication of new titles. This turn towards French also reflects the needs and the social practices of the Greek diaspora, as well as its tendency towards westernisation. The French language is seen by Paris-based Greek editors and journalists as a means which would permit them to intervene in the European discussion about the fate of their country. While very diverse, these periodicals demonstrate the aspirations of the diaspora and are characterised by an ideological coherence which determines, to a great extent, their editorial content. They function as a powerful tool of propaganda for the benefit of the Greek nation and become a focal point for cultural transfers between France and Greece.